Effectiveness of Biofeedback Therapy in Treating Bladder Function Disorders - Admira, Adrie; Mark, Elladdadi; Isneini, Isneini; Joshua, Wang; Suprayitno, Emdat (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Bladder dysfunction is a frequent health problem faced by many individuals around the world. Biofeedback therapy has become an increasingly commonly used approach to address these disorders, focusing on improving pelvic muscle control and body awareness. However, few studies have specifically evaluated the effectiveness of biofeedback therapy in addressing impaired bladder function, especially in specific populations. This study aimed to evaluate the effectiveness of biofeedback therapy in addressing bladder dysfunction in adults with incontinence or urinary retention. This study used a randomized controlled clinical research design. They were randomly divided into two groups, an intervention group that received biofeedback therapy for 8 weeks, and a control group that received no additional intervention. Measurements were made using standardized clinical evaluation scales and objective measurements of urine volume. The results of this study showed that the intervention group receiving biofeedback therapy had significant improvements in pelvic muscle control, incontinence frequency, and volume of retained urine resolved compared to the control group. This improvement was also maintained in the follow-up period after 3 months of intervention. The conclusion of this study is that biofeedback therapy is proven to be effective in overcoming bladder function disorders in adult individuals with complaints of urinary incontinence or retention. This approach can be an effective and sustainable treatment option to improve the quality of life and well-being of individuals affected by bladder dysfunction. Further research is needed to explore more deeply the mechanisms and factors that influence the effectiveness of biofeedback therapy in different cases of bladder function disorders.